Studi Pengaruh Good Corporate Governance Terhadap Praktik Earnings Management pada Perusahaan Terdaftar di PT Bursa Efek Indonesia (Jurnal Manajemen dan Kewirausahaan, 2009)
This research is done for the purpose of finding out the effect of Good Governance practice can reduce earnings management practice done by company. This research uses companies registered in manufacture sector in Indonesia Stock Exchange observation period 2005-2007 as samples. Last sample used in this research is 384 years of observation. This research uses OLS method. The result shows that only 2 variables have significant effect to Earning Management practice which is CEO Duality and controlling shareholder existence. Other independent variables such as independent commissioner and audit committee and also shareholder coalition outside the controlling shareholder don’t have any effect to earning management practice in the company. Control variable like coverage analyst and debt don’t have any effect either, to earning management practice existence.